The relationship between neoliberal belief and socio-political attitude in Japan: conservative psychological tendencies of neoliberals - Kengo Nawata; Toru Oga; Makoto Fujimura (Cogent Psychology)
The study aimed to examine the correlation between neoliberal beliefs and socio-political attitudes in Japan. A comprehensive four-factor scale was customized to assess neoliberal beliefs, making it suitable for Japanese society by creating items that evaluated the four factors and renaming them to align with the Japanese context. This study assesses the following four factors: ‘aversion to reducing inequality,’ ‘endorsement of meritocracy,’ ‘competition,’ and ‘government non-interference.’ Moreover, we incorporated items to gauge ‘personal responsibility,’ which are deemed a fundamental constituent of neoliberalism in Japan but is not directly included in the abovementioned scale. The association between these five sub-components of neoliberal beliefs and socio-political attitudes in Japan, including demographic and psychological variables, attitudes toward policy issues, and political party support, was scrutinized. Our findings consistently demonstrate that neoliberal beliefs are correlated with conservative psychological tendencies.